International Contagion : Implications for Policy - Majnoni, Giovanni, 1954- 1954- (The World Bank, 1999)
March 2000 - What can the international community do to prevent financial contagion? Chang and Majnoni try to identify and evaluate the public policy implications of financial contagion on the basis of a very simple model of financial crises. In this model, financial contagion can be driven by a combination of fundamentals and by self-fulfilling market expectations. The model allows the authors to identify different notions of contagion, especially the distinction between monsoonal effects, spillovers, and switchers between equilibria. They discuss both domestic and international policy options. Domestic policies, they say, should be aimed at reducing financial fragility - that is, reducing unnecessary short-term debt commitments. With explicit commitments, the maturity of external debts should be lengthened. With implicit commitments, such as private liability guarantees, they emphasize limiting or eliminating such guarantees, to improve an economy's international liquidity and reduce its exposure to contagion. Internationally, they stress the need for improving financial standards, which makes it easier to assess when a country is subject to different kinds of contagion. The effectiveness of international rescue packages depends on the kind of contagion to which a country is exposed. Implications: The international community should help those countries that are already helping themselves. This paper - a product of the Financial Sector Strategy and Policy Group - is part of a larger effort in the group to study the determinants and policy implications of international financial contagion. The author Giovanni Majnoni may be contacted at gmajnoni@worldbank.org